ADOBE INDESIGN 2.0 TO MAKING A "WRITING RESEARCH OR SCIENTIFIC WRITING" - Joseph Henry Aribowo; Dewi Melani L SKom, MMSi Dewi Melani L SKom, MMSi (Jurnal Sistem Informasi, 2005)
World of design and layout is a lonely world behind the scenes during thesepublications are being looked at by millions of people. Design and layout also involvea lot of details that need accuracy and diligence in managing every element into asingle unitary design that was seen and at the same time conveying a messageeffectively.Many of the media present information in a presentation this uninteresting,monotonous and less imaginative, so here Writers choose one information mediumthat is becoming BOOK topic in this writing. The book is meant here by the author of"Writing Research or Scientific Writing."By using Adobe InDesign 2.0, the authors will explain how the process to design andarrange the layout of a "Writing Research or Scientific Writing" that can be easilyunderstood the intent and purpose made "Writing Research or Scientific Writing.